A revised subgeneric position for Polypedilum (Probolum) simantokeleum, with description of a new Uresipedilum species in Japan (Diptera: Chironomidae) - Yamamoto, Nao; Yamamoto, Masaru (Zootaxa, 2015)
Two Japanese Polypedilum species including a new species are redescribed and described based on the males. Polypedilum (Probolum) simantokeleum, Sasa, Suzuki et Sakai, 1998, is transferred to the subgenus Uresipedilum. Polypedilum (Uresipedilum) dissimilum sp. nov. is easily distinguished from other members of Uresipedilum by having a T-shaped tergal band. Definition of the subgenus Probolum is briefly discussed: we suggest Probolum should be defined as the species with the superior volsella bearing inner lobe pending adequate larval information.